Mapping Socio-Economic and Entrepreneurial Diversity among Makhana Farmers in Bihar through Cluster Analysis - Kumar Sonu; Kaushal Kumar Jha (Indian Journal of Extension Education, 2025)
Makhana (Euryale ferox), a high-value aquatic crop, plays a pivotal role in the rural economy of Bihar, particularly in the Mithilanchal and Kosi regions. However, the socio-economic characteristics of makhana farmers are far from homogeneous, reflecting diverse livelihood strategies, access to resources, and market participation levels. The study presents a replicable protocol to classify socio-economic and entrepreneurial diversity among makhana farmers. A multistage stratified random sampling technique was used to collect primary data from 120 farmers across four major districts of Bihar during 2022-23. Ward’s hierarchical clustering followed by k-means clustering identified three statistically distinct groups based on landholding, income, and entrepreneurial indicators. ANOVA and Levene’s tests confirmed significant variation across the clusters. The findings support the development of targeted, group-specific extension strategies. The proposed framework serves as a replicable protocol for classifying farmer heterogeneity in similar agricultural contexts. The analysis revealed three distinct clusters of farmers viz., Well-capitalised Makhana Farmers, Progressive and Prosperous Farmers, and Traditional, Medium-Level Farmers—each with unique characteristics and development needs. The findings support the development of targeted, group-specific extension strategies. The proposed framework serves as a replicable protocol for classifying farmer heterogeneity in similar agricultural contexts.